The Vietnam War - Devaney, John. (New York : F. Watts, 1992)
Unveils the horror and the politics of this controversial war, from the French withdrawal after the Battle of Dien Bien Phu to the fall of Saigon in 1975.
Includes bibliographical references (p. 60) and index.
Wilson's Junior High School
School Library Journal
Booklist
5.7
5-8
Keywords: Vietnamese Conflict, 1961-1975 -- Juvenile literature; Vietnamese Conflict, 1961-1975.; Vietnam War, 1961-1975.